Farmers’ Choice of the Modern Rice Varieties in the Rainfed Ecosystem of Nepal - Ganesh Joshi; Siegfried Bauer (Journal of Agriculture and Rural Development in the Tropics and Subtropics, 2006)
In an effort to increase the productivity of rice in Nepal, several modern varieties have been released. Farmers have adopted these varieties to varying degrees depending upon the types of production environment and the considerations for attributes. This paper attempts to identify factors that condition the adoption of selected modern varieties of rice using a multinomial logit model including both production and consumption attributes valued by the farmers and farm and farmer related variables. The results show that both categories of variables are significant in determining the demand for a specific variety. The results of this paper have implications for crop improvement and the modern variety adoption. Research approaches that incorporate farmers’ preferences for various attributes of rice in breeding programs and extension strategies have to be adopted. Various types of methods such as demonstration and farmer- participatory trials could be effective vehicles in this regard. Also the research system should develop a range of varieties in order to meet the multiple concerns of the farmers as a single variety may not be able to fulfill all of their concerns.